Proceso atención de enfermería en gestante de 33 semanas y amenaza de parto pretérmino. - Silva Silva, María Cristina (2024)
Premature labor occurs when a pregnant woman's regular contractions cause the cervix to open after the 19th week and before the 36th week of gestation. Premature labor results in premature birth. When premature birth occurs, the risks to the health of the newborn increase. Some premature babies need special medical care in the neonatal intensive care area. They may also have long-term physical and mental disabilities. The main cause of preterm birth is often not specified. Certain risk factors can increase the chance of preterm birth, but preterm birth can also occur in pregnant women without known risk factors. Which the Nursing Care Process was systematically applied with the nanda, noc and nic taxonomy process to make the nursing diagnosis and then be able to implement the care plan to improve your health.